Improvement of the yield and quality of wheat by seed treatment of biological fertilizers Biofarm and Probio96 under feild condiotions - Soleiman Ghasemi; Masoud Ahmadzadeh; Majid Hosseini; Siavash Torabi (علوم و فناوری بذر ایران, 2019)
In this study, the effects of biological fertilizers Biofarm and Probio96 on quality and yield of wheat were evaluated. The pilot was considered a farm about 5,000 square meters at Khenejin city (Markazi province). A completely randomized block were considered as experimental design. The treatments included in Biofarm, Probio 96 and control. in this study quantitative and qualitative parameters were examined. The results showed that Probio96 with 366.8 plants per square meter resulted in the highest number of germination. The highest plant height was related to treatment Probio 96 to 47.33 cm. About tillering, Biofarm with an average of 3.14 tillers per plant were in first place. Seed treatment by Biofarm and Probio96 improved thousand seed weight to 41.1 and 39.8 gram respectively. This is despite the fact that control resulted in 37.2 g. The results showed that wheat yield in different treatments has significant difference compared to the control. The application of both biological fertilizer increased yield compared to control. Seed treatment with Probio96 and Biofarm increased wheat yield about 44 and 64 percent respectively. The results showed that Probio96 , Biofarm and control resulted in 1900.9, 1661.7 and 1152.8 kg per hectare yield, respectively. Qualitative analysis of wheat production under three different treatments showed that the treatments had no significant effect on wheat grain quality characteristics.